Alley farming in south-western Nigeria. The role of farming systems research in technology Development - Reynolds, L.; Domenico, C.M. di; Atta-Krah, A.N.; Cobbina, J. (Wiley, 1991)
Presents and discusses methods of diagnosing major constraints to crop & livestock production within the farming systems of south-west Nigeria. Examines the Development of the alley farming technology, implementation of on-farm trials, feedback from on-farm research which includes investigations in land tenure & availability, participation by women, agronomic practices, livestock feeding and tree management. Includes data on maize yield from Leucaena farms with & without fallow, effects of supplementary Leucaena & Gliricidia browse on growth & survival of West African Dwarf goats, labour requirements for maize cultivation in farmer-managed trials, quality & frequency of feed given. Also presents data on characteristics of alley farmers & conventional farmers, characteristics of farms, and farmers' perception & uses of alley farms. Ends with a discussion on modifications in farmers' behaviour and lessons for research.